Evaluation of a Multidisciplinary Bachelor Course on Pain with Autonomy-Supportive Teaching Strategies through the Lens of Self-Determination Theory - Adriana H. van Houwelingen; Rashmi A. Kusurkar; Ferdi Engels (MDPI AG, 2021)
To stimulate learners' autonomy, autonomy-supportive teaching strategies were included in the design of a multidisciplinary elective course on pain. During this course, students explored pain from different disciplinary angles, i.e., from biomedical, psychological, arts, philosophical, and anthropological perspectives. In the course, autonomy was stimulated by giving students freedom of choice, especially in their final assignments. The aim of this study was to explore students' freedom of choice and students' perceptions of the multidisciplinary course on pain, particularly students' perception of autonomy in the light of self-determination theory (SDT). To address the aim of this study, a mixed methods approach was used. Directed content analysis was conducted on a reflective part of the final individual assignment and was used to find categories fitting within SDT and also outside it. In addition to this, the diversity of topics as well as different disciplines present in the final individual assignments was explored to demonstrate students' freedom of choice. This study shows that the course setup supported students' autonomy and relatedness and stimulated students' interest in and relevance to pain. Moreover, it stimulated students' freedom of choice and stimulated curiosity towards disciplines such as arts and philosophy. Therefore, it can be concluded that we successfully developed a multidisciplinary course on pain in which students are exposed to different autonomy-supportive teaching strategies based on the SDT framework.